Pengaruh Efektivitas Terapi Musik terhadap Penurunan Nyeri pada Pasien Zam–Zam 1 Rumah Sakit Sultan Hadlirin Jepara - Muhammad Fachrudin; Ratna Ratna; Feri Catur Yuliani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pain is one of the main problems often experienced by patients during treatment in hospitals, including in the Zam-Zam 1 Ward of Sultan Hadlirin Hospital, Jepara. High levels of pain can affect comfort, quality of rest, and slow the patient's healing process. Various non-pharmacological interventions have been developed to help reduce pain, one of which is music therapy, which works through distraction and relaxation mechanisms. This study aims to analyze the effectiveness of music therapy in reducing pain levels in patients in the Zam-Zam 1 Ward of Sultan Hadlirin Hospital, Jepara. The research method used a quasi-experimental design with a pretest-posttest approach without a control group. The study sample consisted of 47 patients who met the inclusion criteria and were selected using a purposive sampling technique. The research instrument used a Numerical Rating Scale (NRS) to measure the patient's pain levels before and after the intervention. The music therapy process was carried out by playing relaxation music for a certain period according to the research procedure. Data analysis was carried out using a paired t-test to determine the difference in pain levels before and after music therapy. The results showed an average decrease in pain levels of 1.79 with a standard deviation of 1.05. The t-test results yielded a t-value of 9.017 with a p-value of 0.000 (p < 0.05), indicating a significant difference between pain levels before and after the intervention. These findings demonstrate that music therapy is effective in reducing pain perception in hospitalized patients. In conclusion, music therapy can be used as an alternative non-pharmacological intervention that is easily implemented by healthcare professionals to improve patient comfort and quality of care in hospitals.